2020
DOI: 10.1002/aic.16909
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization of liquid film behavior during droplets–polyethylene particle collision

Abstract: Nowadays, the droplet–particle collision characteristics in the gas‐phase ethylene polymerization process are still unclear. The high‐speed photography and a quasi‐circle imaging approach are employed to study the collision interaction characteristics between liquid droplets and polyethylene particles. The liquid film evolution is studied through variations of the film thickness on the particle north pole, the dynamic contact angle, center angle and film thickness at the maximum extension. Results have found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Image processing was carried out to extract data from the images taken at different time instants using quasi-circle processing of MATLAB code. It can be divided into two parts, recognition and extraction, which was earlier reported in Ren et al 16 The program stimulates the gray level of all of the pixels to obtain the boundary value. After the particle profile was determined, points on the contour of the particle are collected and fit into a circle multiple times.…”
Section: Image Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Image processing was carried out to extract data from the images taken at different time instants using quasi-circle processing of MATLAB code. It can be divided into two parts, recognition and extraction, which was earlier reported in Ren et al 16 The program stimulates the gray level of all of the pixels to obtain the boundary value. After the particle profile was determined, points on the contour of the particle are collected and fit into a circle multiple times.…”
Section: Image Processingmentioning
confidence: 99%
“…The furthest extended arc length s and center angle φ are both parameters describing the spreading process of the liquid film, so only φ is discussed. The treatment methods are as shown in eqs and , respectively The droplet–particle collisions are usually characterized using dimensionless parameters such as the Weber number, Reynolds number, Capillary number, Ornezog number, etc., which are defined as shown in eqs –.…”
Section: Experimental Arrangementmentioning
confidence: 99%
See 1 more Smart Citation
“…Albeit some studies in literature have considered the assumption of heterogeneous evaporation in FBRs, ,, some experimental studies have further investigated interactions between the particle and droplet. Ren et al studied the collision interaction characteristics between PE particles and liquid droplets by high-speed photography and a quasicircle imaging approach. They have reported that collision of the liquid droplet with PE particle results in stretching and wrapping of PE particle by a liquid film in which a portion of liquid film leaves the particle surface and a small amount of liquid covers the surface.…”
Section: Modeling a Fbrmentioning
confidence: 99%
“…In the previous study, our research team studied the collision process of hydrocarbon droplets with polyethylene particles in detail. Ren et al 13 conducted an experimental study on the collision process between n‐hexane, 1‐hexene droplets, and polyethylene particles. Two kinds of liquid film behaviors were found, named the directly slide and recoil and accompanied by evaporation and splash.…”
Section: Introductionmentioning
confidence: 99%